Visfatin levels and intima-media thicknesses in rheumatic diseases - Ozgen, Metin; Koca, Suleyman Serdar; Aksoy, Kader; Dagli, Necati; Ustundag, Bilal; Isik, Ahmet (Springer London Ltd, 2011)
Chronic inflammatory rheumatic diseases lead to increased prevalence of atherosclerosis. However, this early and accelerated atherosclerosis cannot be explained by traditional cardiovascular risk factors alone. The permanent overexpression of cellular adhesion molecules and pro-inflammatory cytokines in chronic inflammatory conditions may participate in accelerated atherosclerosis. Visfatin, a novel adipocytokine, has a potential insulin-like action and pro-inflammatory effects. Therefore, the aim of the study was to determine serum visfatin level and its association with common carotid intima-media thickness (IMT), which is a predictor of atherosclerosis, in patients with rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), systemic sclerosis (SSc), and Beh double dagger et's disease (BD). The study involved 29 RA, 26 SLE, 25 SSc, 30 BD patients, and 29 healthy controls (HC). Serum levels of TNF-alpha, IL-6, and visfatin were analyzed using enzyme-linked immunosorbent assay method and homeostasis model assessment for insulin resistance (HOMA-IR) indexes, and IMTs were determined. Serum visfatin level was higher in the RA group than all the other groups. In addition, visfatin level was higher in the active BD subgroup than the inactive BD subgroup. In the study groups, visfatin levels were not correlated with HOMA-IR indexes and IMTs. Whereas visfatin serum concentration was not associated with insulin resistance and carotid atherosclerosis in selected rheumatic diseases, it was higher in the RA and active BD groups, but not in the SLE and SSc groups. Visfatin levels may be associated with Th1/Th2 balance. Further studies are needed for more precise elucidation of the pro-inflammatory activities of visfatin.
Keywords: Chronic inflammation; IMT; Insulin resistance; Visfatin